2022
DOI: 10.3390/biomedicines10082032
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuropilin 1 in COVID-19 Patients with Acute Ischemic Stroke

Abstract: Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection can trigger the adaptive and innate immune responses, leading to uncontrolled inflammatory reactions and associated local and systematic tissue damage, along with thromboembolic disorders that may increase the risk of acute ischemic stroke (AIS) in COVID-19 patients. The neuropilin (NRP-1) which is a co-receptor for the vascular endothelial growth factor (VEGF), integrins, and plexins, is involved in the pathogenesis of AIS. NRP-1 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 143 publications
(176 reference statements)
0
26
0
Order By: Relevance
“…Statins are one of the main cornerstone drugs for the management of cardiovascular disorders, regardless of dyslipidemia status via their pleiotropic effects. The increasing use of statins, mainly in the elderly groups for primary and secondary preventions of cardiovascular diseases, makes them a commonly used medication globally [ 32 , 33 , 48 ]. It has been shown that 30% of people in the USA over the age of 40 are on statins [ 32 , 33 , 35 ].…”
Section: Statins and Admentioning
confidence: 99%
“…Statins are one of the main cornerstone drugs for the management of cardiovascular disorders, regardless of dyslipidemia status via their pleiotropic effects. The increasing use of statins, mainly in the elderly groups for primary and secondary preventions of cardiovascular diseases, makes them a commonly used medication globally [ 32 , 33 , 48 ]. It has been shown that 30% of people in the USA over the age of 40 are on statins [ 32 , 33 , 35 ].…”
Section: Statins and Admentioning
confidence: 99%
“…Thus, female sex is regarded as a potential risk factor for the development of PSC due to higher immunological response and hormonal changes [ 48 ]. However, some studies found no gender difference in the risk of developing PCS after an acute SARS-CoV-2 infection [ 49 , 50 ]. Furthermore, co-morbidities, advanced age, and the severity of the initial disease are associated with an increased risk of developing PCS [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species play crucial roles in cancer initiation, and progression and elevated levels were observed in malignant cells compared with their regular counterparts [ 26 , 27 ]. Several anti-oxidative compounds have been shown to protect against experimental carcinogenesis and induce the apoptosis of cancer cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%